Risk assessment of contrast-induced acute kidney injury in patients with acute myocardial infarction after coronary angiography and percutaneous coronary intervention - A. A. Ursta; E. I. Kharkov; M. M. Petrova; A. R. Kotikov; O. V. Ursta (Российский кардиологический журнал, 2021)
Aim. To assess the risk of contrast-induced acute renal injury (CI-AKI) in patients with acute myocardial infarction in a highly specialized hospital after coronary angiography.Material and methods. The study sample included 502 patients who were treated in the cardiology department of a specialized hospital. CI-AKI was established by an increase in creatinine >26 μmol/L within 48 hours after percutaneous coronary intervention (PCI) with radiopaque contrast agents or an increase in creatinine >50% within a week after PCI. A multistage statistical analysis was used to search for possible predictors of CI-AKI.Results. In total, CI-AKI was diagnosed in 57 (11,3%) patients. Based on the analysis performed, 3 significant predictors of CI-AKI were identified: patient’s age, contrast medium volume (ml/kg) and anemia (presence/absence). An equation for assessing the risk of CI-AKI in patients after PCI has been created.Conclusion. A simple scale for assessing the CI-AKI risk makes it possible to identify a category of patients who requires preventive measures to reduce iatrogenic complications and mortality.